2019
DOI: 10.1007/s11412-019-09296-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of vocational students’ collaboration and knowledge acquisition through instruction and joint reflection

Abstract: New societal demands call for schools to train students' collaboration skills. However, research thus far has focused mainly on promoting collaboration to facilitate knowledge acquisition and has rarely provided insight into how to train students' collaboration skills. This study demonstrates the positive effects on the quality of students' collaboration and their knowledge acquisition of an instructional approach that consists of conventional instruction and an online tool that fosters students' joint reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 53 publications
(93 reference statements)
1
42
0
Order By: Relevance
“…This is in line with research conducted by Brindley, Walti, & Blaschke that at the time of collaboration, students share their knowledge so that they obtain richer knowledge through joint exploration and the achievement of shared meanings [47]. Other research results also show that collaborative activities make students more involved in the learning process so that it leads to increased mastery of concepts [48], [49].…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with research conducted by Brindley, Walti, & Blaschke that at the time of collaboration, students share their knowledge so that they obtain richer knowledge through joint exploration and the achievement of shared meanings [47]. Other research results also show that collaborative activities make students more involved in the learning process so that it leads to increased mastery of concepts [48], [49].…”
Section: Discussionsupporting
confidence: 87%
“…The aim of computer simulation in computer supported collaborative learning (CSCL) studies is to scaffold collaborative learning process on a contextualized environment that helps students achieve deeper understanding through shared problematizing (Pietarinen et al, 2021). The study conducted by Eshuis et al (2019) prompted students to learn with computer simulations and guided them to reflect upon the collaboration activities to acquire both science knowledge and collaboration skills. A new form of computer simulations, collaborative simulations, are available on some online platforms, which support students at distributed locations to synchronously collaborate on the simulations to learn sciences.…”
Section: Collaborative Computer Simulationsmentioning
confidence: 99%
“…In a recent study, however, Chang et al () found that not all collaborative groups learning with an online simulation were able to engage in a productive collaboration process; obviously, collaboration between students also needs to be trained or supported. In a recent study on learning with a simulation of energy transport systems, Eshuis et al (in press) compared students who received instruction about collaboration with students who received this instruction plus a tool that visualized their own assessment of the collaboration process and that prompted them to reflect on their collaboration. These authors found that the latter group outperformed the first on a number of central collaboration processes and on a resulting knowledge test.…”
Section: The Next Steps In Technology‐based Guidance Of the Inquiry Pmentioning
confidence: 99%